Biodegradable Poly (Lactic Acid) Synthesis, Modification, Processing and Applications - Ren, Jie (Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Biodegradable Poly (Lactic Acid): Synthesis, Modification, Processing and Applications" describes the preparation, modification, processing, and the research and applications of biodegradable poly (lactic acid), which belong to the biomedical and environment-friendly materials. Highly illustrated, the book introduces systematically the synthesis, physical and chemical modifications, and the latest developments of research and applications of poly (lactic acid) in biomedical materials. The book is intended for researchers and graduate students in the fields of materials science and engineering, polymer science and engineering, biomedicine, chemistry, environmental sciences, textile science and engineering, package materials, and so on. Dr. Jie Ren is a professor at the Institute of Nano and Bio-Polymeric Materials, School of Material Science and Engineering, Tongji University, Shanghai, China.